CAPITAL INVENTORY/ASSET DISPOSAL USING SAP S/4HANA IN FIELD INVENTORY MANAGEMENT (FIM) - Madhava Rao Kunchala, (INTERNATIONAL JOURNAL OF COMPUTER ENGINEERING AND TECHNOLOGY (IJCET), 2024)
Building upon the earlier discourse on Asset Capitalization and Transfer (ref (Asset Capitalization using SAP S4/HANA in Field inventory management (FIM), 2024) and (CAPITAL INVENTORY/ASSET TRANSFER USING SAP S/4HANA IN FIELD INVENTORY MANAGEMENT (FIM), 2024) using SAP S/4HANA in Field Inventory Management (FIM) this abstract delves into Asset disposal or scrapping is a crucial aspect of asset management, particularly in the context of Field Inventory Management (FIM) within SAP S/4HANA. This abstract explores the processes and functionalities involved in asset disposal or scrapping using SAP S/4HANA's FIM module. It delves into the intricacies of managing asset disposal transactions, ensuring compliance with regulatory requirements, and optimizing asset utilization. This abstract delves into the specialized processes and functionalities involved in asset disposal or scrapping using SAP S/4HANA's FIM module in medical industries.